Foreign Direct Investment: A doubtful blessing? A fuzzy-set QCA approach - Castillo Castañeda, Alberto; Gil-Barragán, Juan Manuel; Torres, Michael (Cooperativismo & Desarrollo, 2021)
The article starts from the analysis of the main theoretical economic works on Foreign Direct Investment (FDI) to extrapolate argumentatively what has been the influence, whether positive or negative, in the economic growth of the states. Once some relevant FDI factors in economic growth have been inductively identified, this study uses fuzzy-set qualitative comparative analysis (fsQCA) to identify the combinations of factors that a country must coordinate for FDI to have a positive impact on its economic growth. For this purpose, we use data from Brazil, Russia, India, China, and South Africa (BRICS)
Keywords: BRICS; fuzzy-set qualitative comparative analysis (FsQCA); foreign direct investment; economic growth